Kemampuan Guru SMK Mengimplementasikan Artificial Intelligence dalam Perangkat Ajar - Sumardi, Kamin; Rohendi, Dedi; Saripudin, Saripudin; Ramadhan, Muhammad Oka (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The implementation of the Merdeka Curriculum prioritizes a differentiated approach in its learning process. Differentiation is clearly achieved by grouping students' learning outcomes based on their growth phases. The Merdeka Curriculum accommodates six phases: Phase A, B, C, D, E, and F. These phases are designed to build effective learning and achieve learning objectives in a timely manner. Effective learning must be supported by high-quality teaching materials, which in turn will support efficient learning time, active student engagement, and quality education. Artificial Intelligence (AI technology can assist teachers in creating good and high-quality teaching materials. This community service activity employs an in-house training method with persuasive, collaborative, and participatory approaches. The training was conducted over two days, on Friday and Saturday, July 19-20, 2024, at SMKN 1 Cinangka, Serang Regency, Banten. The materials covered included creating e-modules and scientific papers with the help of AI. The training was attended by 55 participants. The results of the training indicate that, on average, 69% of vocational school teachers already have knowledge about AI, 57% have an understanding of AI, and 69% have implemented AI in their teaching materials. Overall, the training results show that 65% of the participants have acquired basic skills in creating e-modules and scientific papers with the help of AI. Therefore, com\munity service through AI training is very much needed by vocational school teachers.